Artesunate/Amodiaquine Versus Artemether/Lumefantrine for the Treatment of Uncomplicated Malaria in Uganda: A Randomized Trial - Yeka, Adoke (J Infect Dis, 2016)
Background. In treating malaria in Uganda, artemether-lumefantrine (AL) has been associated with a lower risk of recurrent parasitemia, compared with artesunate-amodiaquine (AS/AQ), but changing treatment practices may have altered parasite susceptibility. Methods. We enrolled 602 children aged 6–59 months with uncomplicated falciparum malaria from 3 health centers in 2013–2014 and randomly assigned them to receive treatment with AS/AQ or AL. Primary outcomes were risks of recurrent parasitemia within 28 days, with or without adjustment to distinguish recrudescence from new infection. Drug safety and tolerability and Plasmodium falciparum resistance–mediating polymorphisms were assessed. Results. Of enrolled patients, 594 (98.7%) completed the 28-day study. Risks of recurrent parasitemia were lower with AS/AQ at all 3 sites (overall, 28.6% vs 44.6%; P < .001). Recrudescences were uncommon, and all occurred after AL treatment (0% vs 2.5%; P = .006). Recovery of the hemoglobin level was greater with AS/AQ (1.73 vs 1.39 g/dL; P = .04). Both regimens were well tolerated; serious adverse events were uncommon (1.7% in the AS/AQ group and 1.0% in the AL group). AS/AQ selected for mutant pfcrt/pfmdr1 polymorphisms and AL for wild-type pfcrt/pfmdr1 polymorphisms associated with altered drug susceptibility. Conclusions. AS/AQ treatment was followed by fewer recurrences than AL treatment, contrasting with older data. Each regimen selected for polymorphisms associated with decreased treatment response. Research should consider multiple or rotating regimens to maintain treatment efficacies.